Evolving financial markets and international capital flows : Britain, the Americas, and Australia, 1865-1914 - Davis, Lance E. (Lance Edwin) (Japan-U.S. Center Sanwa monographs on international financial markets., 2001)
"This study examines the impact of British capital flows on the evolution of capital markets in four countries - Argentina, Australia, Canada, and the United States - over the years 1865 to 1914"--Jacket